Developing cooperative integrated reading and composition-based role-playing game application as an alternative media in the reading learning - Nina Sofiana (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2018)
The objective of this study is to develop Role-Playing Game (RPG) application as an alternative media in reading learning. The developed RPG application is based on Cooperative Integrated Reading and Composition (CIRC). The implementation of the developed RPG application is aimed to provide learning materials of reading skill in more attractive way to generate an innovative learning environment in which the students will not be uninterested in the learning process. The study is education research and development (R&D) which consisted of research and information collecting, planning, developing product form, expert validation, product revision, field testing and developing final product. The subjects are the students and English teachers from one of vocational schools in Pati, Central Java, Indonesia. The instruments of this research are observation, documentation and questionnaire. Using qualitative and quantitative data analysis, the media developed contained some texts and it belonged to good category as the result of validation from material and media experts. After the developed media was used in reading learning, it was found that the students had positive response toward it. Thus, it can be deduced that the RPG application developed can be used as a media in learning process of reading skill.